TRUMP’S TWITTER EFFECT ON FINANCIAL INDEXES - Dumrongvachiraphan, Wasawat; Tangjitprom, Nopphon (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
This study investigates the impact of Trump’s tweets on abnormal returns and trading volumes of the S&P 500, using VADER to determine the sentiment of the daily tweets to identify relevant events. Based on the daily tweets from U.S President Donald Trump’s twitter account from 1st January 2018 to 16th December 2019, about 20 event samples had been identified. Statistical analysis using event study techniques demonstrated that only negative tweets could lead to statistically significant abnormal return and trading volumes over 1 or 2 trading days after the tweets. The study did not find any statistically significant relationship among positive tweets, abnormal returns, and trading volumes. According to the analysis, the conclusion of these results demonstrates that Trump’s tweet is still another source of information used to predict the U.S stock market return.